Smart Attendance Tracking: QR Codes for Easy Classroom Management - B. Senthilraja; D. Narmadha; S. Rupika (International Journal of Electronics Automation, 2024)
This study introduces a simple yet powerful way to track attendance in schools and universities using QR codes. Instead of the traditional, often slow, and error-prone manual methods, this digital QR-based system speeds up the process and makes it easier for both students and teachers. With a unique QR code for each person, students can quickly scan their code with their smartphones to mark their attendance. This approach reduces mistakes and prevents "proxy attendance," where friends might sign in for each other. One of the best parts is that the system is affordable, doesn’t need much setup, and works smoothly with mobile devices, helping everyone stay connected. Plus, by cutting down on paper use, it supports environmentally friendly practices. To guarantee that no one's attendance is missed in the event of technological difficulties, such as bad internet, backup solutions, such as temporary manual entry, can be employed. This flexible system works well in various educational settings, from classrooms and labs to online courses, as technology progresses, it could incorporate new features like data tracking to monitor attendance trends or even biometric authentication for added security. All in all, this QR-based attendance system is a secure, effective, and scalable solution that meets the changing needs of modern education.
Keywords: QR code; Teacher; admin; attendance; student